A decade of collaboration in medicines regulation: healthcare professionals engaging with the European Medicines Agency - Ivana Silva; Giulia Gabrielli; Juan Garcia Burgos; Isabelle Moulon; Gonzalo Calvo Rojas; Ulrich Jaeger; Ulrich Jaeger; Rosa Giuliani (Frontiers in Medicine, 2024)
The article shows that the input given by healthcare professionals (HCPs) adds value to the regulatory processes surrounding the development, authorisation, and monitoring of a medicine, but is also an instrument for accountability, trust, mutual exchange as well as an insight into the public health issues that matter most to one of the key stakeholder groups the Agency works with. We highlight the role of HCPs in the EU regulatory process and take stock of the first 10 years of the Framework for Interaction with HCPs to describe how practises have evolved over this time to meet the goals of informing, consulting and improving trust in the EU regulatory system. We will analyse what led European Medicines Agency (EMA) to develop this framework through to the next steps and where the interaction might lead in the future.